Koliko časa porabi zdravnik splošne medicine za administrativna opravila? - Govc Eržen, Jana (Zdravstveno varstvo, 2004)
Introduction. The aim of the study was to determine the amount of time that general practitioners (GPs )in the Celje Health Centre spend on administrativetasks. Methods. In the first phase of the study, seven GPs measured the amount of time needed to carry out individual administrative procedures; for each, five measurements were done. The average time measured was considered the reference time required for individual administrative tasks. In the second phase, 18 GPs were invited to record all administrative tasks performed during five working days. On the basis of the data provided the amount of time needed for administrative operations was computed. Results.On average, GPs spent 21% of their consulting time on administrative work. During that time they completed on average 95 forms for 51 patients, mostly prescriptions (63) and referrals for specialist consultation or hospital admission (11). As much as 26.5% of the time dedicated to administrative tasks was spent on filling in forms for disability benefit applicants and 24.9% for writing out prescriptions. Conclusion. Setting up an effective information system and rationalizing administrative tasks, as well as ensuring closer cooperation of all those involved in treatment, are urgently needed to reduce the amount of paper work in general practice, and thereby enable GPs to spend more time with their patients.
Keywords: administracija; splošna medicina; zdravniki